2016
DOI: 10.1111/jce.12886
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Contact‐Force Sensing Electrophysiological Catheters: How Accurate Is the Technology?

Abstract: Catheter force measurements using the ST SF catheters show a high level of accuracy regarding differences to reference measurements and reproducibility. The reduced accuracy in measurements of 90° acting forces (parallel contact) might be clinically important when creating, for example, linear lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…This finding is in accordance with a previous study by Yokoyama et al, in which the correlation between the reference force and the force measured by TCQ was high (R 2 > 0.988) and not significantly different between the 3 tested angles . In contrast, in a previous study we showed that the accuracy of an electromagnetic CF sensing technology (SmartTouch SF) is indeed affected by the angle of the acting forces, being significantly lower with the catheter tip in a parallel orientation (6.6 g vs. ≤1.2 g; P < 0.01) . This difference might be explained by the difference in the CF sensing mechanism of the electromagnetic and fiber‐optic technologies (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is in accordance with a previous study by Yokoyama et al, in which the correlation between the reference force and the force measured by TCQ was high (R 2 > 0.988) and not significantly different between the 3 tested angles . In contrast, in a previous study we showed that the accuracy of an electromagnetic CF sensing technology (SmartTouch SF) is indeed affected by the angle of the acting forces, being significantly lower with the catheter tip in a parallel orientation (6.6 g vs. ≤1.2 g; P < 0.01) . This difference might be explained by the difference in the CF sensing mechanism of the electromagnetic and fiber‐optic technologies (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the known spring characteristics, the system can convert the tip deflection into CF (amount and orientation) . Therefore, CF measurements are based on changes of the relative position between the transmitter coil and the location sensors: very lateral forces can cause a deflection not only of the distal catheter tip, but also of more proximal parts of the tip (proximal to the spring), where the sensors are located, translating in underestimation of the CF force . On the other hand, in the fiberoptic CF sensing mechanism the acting forces are detected across the whole deformable body, located between electrodes 1 and 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Practically, it is impossible to reach 10 to 20 g at each RF site Moreover, calculation of CF (and FTI) might be inaccurate because of inadequate calibration, contact with neighboring electrodes, or the angle of incidence (underestimation when parallel contact). 21 Finally, FTI as a marker of lesion quality suffers from 2 major limitations: first, FTI (calculated as the product of force by application time) suggests a linear lesion formation during ablation, whereas it is known that lesion volume growth describes a monoexponential curve. 15 Second, FTI ignores the important and evident role of power delivery in lesion creation.…”
Section: Time Of Rf Application Power and Cf As Targets For Rf Ablamentioning
confidence: 99%
“…1 RF energy creates lesions through resistive heating of the subendocardium and heat is thermally conducted to the surrounding tissue. Mechanical and electrical coupling at the electrode-tissue interface are critical factors for lesion formation during RF ablation.…”
Section: Introductionmentioning
confidence: 99%